Recess Quality and Social and Behavioral Health in Elementary School Students. (7th July 2021) - Massey, William V.; Thalken, Janelle; Szarabajko, Alexandra; Neilson, Laura; Geldhof, John
ABSTRACT: BACKGROUND: A majority of research findings have focused on recess as instrumental to achieving minutes of physical activity rather than focusing on the psycho‐social benefits associated with a high‐quality recess environment. The purpose of the current study was to examine the relationship between recess quality and teacher‐reported social, emotional, and behavioral outcomes in children. METHODS: Data were collected from 26 schools in 4 different regions of the United States. Teachers (N = 113) completed behavioral assessments for randomly selected children in their classrooms (N = 352). Data assessors conducted live observations of recess using the Great Recess Framework—Observational Tool. A series of 2‐level regression models were fit in Mplus v. 8.2 to assess how recess quality was associated with indicators of children's social, emotional, and behavioral health. RESULTS: Recess quality significantly predicted executive functioning problems (b = −.360, p = .021), resilience (b = .369, p = .016), emotional self‐control (b = −.367, p = .016), and a composite of adaptive classroom behaviors (b = .321, p = .030). CONCLUSION: Results of the present study demonstrate that recess quality impacts child developmental outcomes. Schools should ensure there is adequate training and resources to facilitate a positive and meaningful recess for students.